Chitinophaga lutea sp. nov., isolated from arsenic-contaminated soil. Issue 7 (17th May 2019) - Zong, Yuanyuan; Wu, Minghan; Liu, Xiaoxiao; Jin, Yongmei; Wang, Gejiao; Li, Mingshun
Abstract : A yellow-coloured bacterial strain, designated ZY74 T, was isolated from arsenic contaminated soil (34 mg kg −1 ) sample collected in Longkou, Hubei Province, PR China. Cells were Gram-stain-negative, aerobic, non-motile and rod-shaped. Strain ZY74 T produced round, yellow-pigmented, smooth and opaque colonies. Based on the results of 16S rRNA gene sequence analysis, strain ZY74 T was found to be affiliated with members of the genus Chitinophaga . Its closest members were Chitinophagabarathri YLT18 T (97.72 %) and Chitinophaganiabensis JS13-10 T (97.17 %). The genome size of strain ZY74 T was 6.61 Mb, containing 5351 predicted protein-coding genes, with a DNA G+C content of 55.0 mol%. The average nucleotide identity values of strain ZY74 T with C. barathri YLT18 T and C. niabensis DSM 24787 T were 76.12 and 73.32 %, respectively. The digital DNA–DNA hybridization values of strain ZY74 T with C. barathri YLT18 T and C. niabensis JS13-10 T were 20.60 and 19.40 %, respectively. The major respiratory quinone was menaquinone 7 and the predominant fatty acids (>5 %) were iso-C15:0, C16 : 1 ω5 c and iso-C17 : 0 3-OH. On the basis of phylogenetic, genotypic, phenotypic and chemotaxonomic characterization, strain ZY74 T represents a novel species in the genus Chitinophaga, for which the name Chitinophaga lutea sp. nov. is proposed. The type strain is ZY74 T (=CCTCC AB2018369 T =KCTC 72039 T ).